KEANEKARAGAMAN KUALIFIKASI ORGAN TATA KELOLA PERUSAHAN SEKTOR PERTAMBANGAN INDONESIA - Ilona, Desi (Gapenas Publisher, 2024)
This study employs a quantitative research method using secondary data from nine mining companies listed on the Indonesia Stock Exchange over the period 2004–2017. The research aims to investigate the relationship between capital structure—specifically leverage levels—and the qualification diversity of both supervisory and management boards. Board qualification diversity is measured based on educational background and professional experience, while leverage is calculated using the debt-to-asset ratio. Companies are grouped into high-leverage and low-leverage categories based on the median split method. Descriptive statistics are used to understand the general characteristics of the data, while independent samples t-tests are applied to examine whether there are statistically significant differences in board qualification diversity between the two leverage groups. Additionally, effect sizes (Cohen’s d, Hedges’ correction, and Glass’s delta) are computed to assess the magnitude of the differences. Statistical analyses are conducted using SPSS software, with a significance threshold of 0.05. This methodological approach allows for a robust comparison of how capital structure may be associated with variations in the composition and qualifications of corporate boards in the Indonesian mining industry